Desain Laporan Keuangan Berdasarkan SAK EMKM Pada “Gerai Pangan Kita” Manado - Carmenita K. I Lelemboto; Erika F Lambonan; Ivoletti M Walukow; Jerry Sonny Lintong; Revleen M. Kaparang (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
This study aims to find out the model for presenting financial statements made by our food house, the obstacles faced by entity managers, and provide solutions on how to present comprehensive financial statements, so that they are useful for stakeholders in decision making. This type of research is a qualitative research, which uses descriptive analysis, with data collection methods in the form of interviews, field observations, and analysis of documents made by the entity. This study found that the financial statements made by RPK were only the realization of cash receipts and disbursements, so that stakeholders could not know for sure how many assets, profits or losses were from the business.